Peran Account Executive dalam Proses Perencanaan Iklan di Era Digital: Perspektif dan Tantangan - Disa Prihantini Kusuma; Aminah Swarnawati (Dinasti Research, 2024)
The advertising industry is experiencing rapid development, with advertisements that were originally only present in conventional media such as television, radio, and print media, now expanding to digital media. Advertising is a dynamic field and always keeps up with the times according to market preferences. Account executives are responsible for the advertising communication system, so in planning advertisements, they must understand the process of persuasion and effective communication. This research uses the literature study method as the main approach to conduct research that aims to investigate the role of Account Executives (AEs) in the advertising planning process in the digital era. The results show that the role of the account executive (AE) in the advertising industry has undergone a profound transformation along with the rapid development of digital technology. The challenges faced by AEs in carrying out their role in the digital era are not small. They must be able to deal with various technological and algorithmic changes that occur rapidly, as well as respond to increasingly fierce competition in the advertising industry.